A COMPARISON OF BODY MASS INDEX AND WEIGHT GAIN AMONG MALE SPRAGUE DAWLEY RATS ON BROILER AND DOMESTIC CHICKEN MEAT FEED - Khan, Hammad Gul; Rashid, Amir; Khan, Zainab; Aman, Faiza; Shoaib, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective:To compare and evaluate the effects of broiler chicken fed with commercially offered feed and chicken fed with organic diet on BMI and weight gain in Sprague Dawley rats.Study Design:A randomized controlled trial.Place and Duration of Study:Multi-Disciplinary Laboratory of Department of Biochemistry and Molecular Biology, Army Medical College, Rawalpindi, and collaborated with Quaid-e-Azam University, Islamabad from November 2017 to April 2019.Methodology:Ninety male early weaned Sprague Dawley rats were arbitrarily assorted into three groups (n=30).Group I control rats were nourished on standard pelleted diet. Group II rats were nourished with organic chicken meat along with their standard pelleted diet. Group III rats were nourished with broiler chicken meat along with their standard pelleted diet.BMI and weight gain were estimated. All variables were calculated as Mean ± SD values. One-way ANOVA was applied to determine the significance among groups followed by Tuckey’s HSD post hoc test. p value ≤ 0.05 was considered significant.Results:The current study demonstrated significant increase in BMI (p ≤ 0.001) and weight gain (p ≤ 0.001) in both experimental groups as compared to control group.Conclusion: Based on the findings of our study we propose that broiler chicken meat consumption could be the probable cause of weight imbalances and out of proportion gain of weight and growth in experimental rats.